2017
DOI: 10.1161/jaha.116.005247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Achieved Blood Pressure on First Stroke in Uncomplicated Grade 1 Hypertension

Abstract: BackgroundWe aimed to test the impact of achieved blood pressure (BP) on first stroke among patients with grade 1 hypertension and without cardiovascular diseases in the China Stroke Primary Prevention Trial.Methods and ResultsA total of 3187 patients with uncomplicated grade 1 hypertension were included. The risk of outcomes was assessed according to: (1) the proportion of visits in which BP was reduced to <140/90 mm Hg, and (2) the time‐averaged systolic BP (SBP) or diastolic BP levels during the study treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…; Qin et al. ). The Framingham study reported reductions in the DBP in the elderly thereby elevating the PP (Franklin et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Qin et al. ). The Framingham study reported reductions in the DBP in the elderly thereby elevating the PP (Franklin et al.…”
Section: Discussionmentioning
confidence: 98%
“… 1 , 2 Hypertension is one of the most important risk factors for stroke. 3 , 4 As the traditional risk factors cannot account for all stroke risk, it is of great clinical importance to identify more modifiable risk factors to improve primary prevention of stroke and reduce the related severe disease burden, especially in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 28 , 29 , 30 When it comes to the lower threshold of BP, a post hoc analysis of the China Stroke Primary Prevention Trial (CSPPT) presented that a SBP of less than 120 mmHg was associated with an increasing risk of stroke and all‐cause mortality. 31 However, it remains unclear due to the lack of robust evidence. We suggest that antihypertensive treatment should be individualized based on tolerability and frailty.…”
Section: Introductionmentioning
confidence: 99%